Diabetic Retinopathy Current Pharmacologic Treatment and Emerging Strategies - Stewart, Michael W.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Adis, 2017)
A well-illustrated and comprehensive analysis of the treatment of diabetic retinopathy, this book covers current treatment options and guidelines, whilst also providing a detailed discussion of emerging therapeutic targets. Existing therapeutic options are covered in depth, with a major focus on anti-vascular endothelial growth factor drugs and sustained release corticosteroids, including a review of trial results supporting current treatment guidelines. The use of agents off-label is also discussed. Controversial topics are discussed in detail with an emphasis on helping the reader make informed decisions, particularly when treating patients for which several treatment approaches may be appropriate because trial data does not clearly define the best option. Emerging therapeutic areas are evaluated, as work continues to identify agents that produce superior morphologic responses and visual acuity gains by targeting other molecules that contribute to diabetic retinopathy. Promising new drugs, targets and delivery systems are identified, and their development analysed.
1. Diabetes and Diabetic Retinopathy: Overview Of A World-Wide Epidemic -- 2. The Diabetic Retina: Anatomy and Pathophysiology -- 3. Treatment of Diabetic Retinopathy: A Historical Perspective -- 4. Targeting Vascular Endothelial Growth Factor -- 5. Corticosteroids: Targeting Multiple Cytokines and Chemokines -- 6. Current Treatment Recommendations -- 7. Vitreolysis: Targeting the Vitreoretinal Interface -- 8. Investigational Medications -- 9. Safety Considerations of Pharmacotherapy -- 10. Socioeconomic Cost of Diabetic Retinopathy and Therapy.
Keywords: Medicine; Diabetes; Ophthalmology; Medicine & Public Health; Diabetes; Ophthalmology